Recombinant Enzymatic Redox Systems for Preparation of Aroma Compounds by Biotransformation - Varga, Viktor; Štefuca, Vladimír; Mihálová, Lenka; Levarski, Zdenko; Struhárňanská, Eva; Blaško, Jaroslav; Kubinec, Robert; Farkaš, Pavel; Sitkey, Vladimír; Turňa, Ján; Rosenberg, Michal; Stuchlík, Stanislav (Frontiers in Microbiology, 2021)
In recent years, the demand for natural aromas and food additives has been constantly growing, which can no longer be saturated with isolation from natural materials. One of the options for improving the availability of natural aroma chemicals is their preparation by enzymatic transformations from suitable precursors. Recombinant enzymes are increasingly being used for this purpose. The target of this work was to develop immobilized enzyme systems for reduction of carbonyl compounds to corresponding alcohols. Here, we studied trans-2-hexenal bioreduction by recombinant Saccharomyces cerevisiae alcohol dehydrogenase (ScADH1) with simultaneous NADH regeneration by recombinant Candida boidinii formate dehydrogenase (FDH). In a laboratory bioreactor with two immobilized enzymes 88 % of trans-2-hexenal was transformed to trans-2-hexenal at 3.7 mmol/L initial substrate concentration. It was found that the aldehyde had negative effect to the ScADH1 stability by eluting Zn2+ ions from the enzyme molecule. Fed-batch operation was used as well, with trans-2-hexenal added in portions with the aim of keeping its concentration at lower level in order to limit the effect of zinc ion elution from the immobilized ScADH1. A similar immobilized two-enzyme system was used for acetophenone reduction to (S)-1-phenylethanol, with another type of recombinant alcohol dehydrogenase (RrADH), from Rhodococcus ruber. The biocatalytic system was successfully tested and provided final conversion of acetophenone to (S)-1-phenylethanol of 61 % at 8.3 mmol/L initial substrate concentration. All used enzymes were immobilized via poly-His tag to Ni2+ activated support giving the advantage of strong but reversible sorption enabling reuse of the carrier after enzyme activity loss.